Association between snus use over time and smoking cessation in Norwegian smokers. (23rd October 2019) - Lund, Ingeborg; Christiansen, Solveig Glestad
Abstract: Background and Aims: The effect of snus (Swedish moist snuff) use over time on smoking cessation has not been clearly established. This study aimed to assess whether there is an association between snus use over the life‐span and smoking cessation in Norway. Design and Setting: Yearly national cross‐sectional surveys (2007–17) among Norwegian adults. Participants: A total of 5353 ever‐daily smokers aged 16–79 years, 61.0% of whom ( n  = 3268) had quit daily smoking, and 16.9% ( n  = 903) were ever snus users. Measurements: Retrospective data on smoking and snus use initiation and smoking cessation. Cox proportional hazard models were applied to estimate the association between time from initiation of snus use and quitting smoking. Findings: There was a significant association between snus use and quitting smoking during the 5 first years after starting using snus (hazard ratio = 1.92, confidence interval = 1.62–2.26), but not thereafter. Conclusion: In Norway, snus use appears to be associated with a higher likelihood of quitting smoking within the first 5 years of initiation of this use.